Development of canned chicken sandwich spread (Gallus domesticus Linn) - Linchangco, Esperanza P.
This study was undertaken to develop a standard procedure for canning chicken sandwich spread. A satisfactory recipe was formulated by first choosing what binder to use, cornstarch or all-purpose flour, then varying the amount of binder chosen. All-purpose flour was found to be a better binder than cornstarch. To determine an adequate processing time and temperature, time-temperature combinations of 50 minutes at 250°F and 60 minutes at 250°F were tested. Base on the results of heat penetration study, physico-chemical and cut-out tests and the microbiological examination of the canned products, time-temperature combination of 50 minutes at 250°F was established to be better of the two combinations studied. The acceptability of the developed product was evaluated using the descriptive method and the hedonic rating. Results were analyzed using analysis of variance (ANOVA). Two samples, Batch A (8.74% flour) and Batch B (12% flour), were found to have no significant difference at the 5% level. Both were found to be moderately acceptable, using the hedonic rating. A cost evaluation showed that Batch A (P4.76/can) is only P0.04 cheaper than Batch B(P4.80).